Cinzas volantes e zeólitas sintéticas na composição da pasta de cimento classe G e degradação por CO2 em condições de armazenamento geológico de carbono - Ledesma, Roger Braun (2018)
Developing technologies for the capture and geological storage of CO2 has been a constant challenge of the scientific community in the search for solutions that can reduce the environmental impacts caused by the release of this gas into the atmosphere. However, its storage in depleted oil wells has been shown to be a very important point, since the materials applied in wells can suffer degradation in the presence of CO2 in the supercritical state and at high pressures. The objective of this work is to evaluate the performance of the class G cement paste used in cementation of wellbore under conditions of geological carbon storage with replacement of part of the cement by pozoanic materials such as fly ash from the fossil fuel burning of the Candiota Thermoelectric Plant, and synthetic zeolites (4A-1 e 4A-2). The contents of the pozalanas used in substitution of the cement were 5% and 10% in weight. The medium in which samples were submitted for degradation tests was CO2 saturated water at 15 MPa pressure and 90 °C for 7 and 14 days. Scanning Electron Microscopy (SEM), XRay Diffraction (XRD) and compressive strength tests were the characterization techniques used in this work. The results showed that the use of fly ash increased the compressive strength of the samples after 14 days, mainly for higher percentage of cement replacement by this material (10%), but its chemical degraded layer increased. In case of zeolites 4A-1 use, a lower compressive strength was observed compared to the standard paste, but the degraded layer was reduced. When zeolites 4A-2 were used significant loss of compressive strength was observed from 7 to 14 days, mainly for the proportion of the mixture of 10% and its degraded layer also reduced.